2018
DOI: 10.3762/bjoc.14.171
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of boron-dipyrromethene (BODIPY) reporter dyes for cucurbit[7]uril

Abstract: We introduce herein boron-dipyrromethene (BODIPY) dyes as a new class of fluorophores for the design of reporter dyes for supramolecular host–guest complex formation with cucurbit[7]uril (CB7). The BODIPYs contain a protonatable aniline nitrogen in the meso-position of the BODIPY chromophore, which was functionalized with known binding motifs for CB7. The unprotonated dyes show low fluorescence due to photoinduced electron transfer (PET), whereas the protonated dyes are highly fluorescent. Encapsulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 72 publications
(87 reference statements)
0
11
0
1
Order By: Relevance
“…Despite numerous attempts and alternative strategies for completing the synthesis of the platform using the F-BODIPY uorophore, the route was unsuccessful resulting in either BF 2 core removal or complete decomposition (see Supplementary Material), despite there being reports in the literature of similar transformations being successful in the presence of F-BODIPY dyes. [24][25][26][27][28] This documented instability of the BF 2 core [29][30][31][32][33][34][35][36] was overcome by replacing it with the recently reported 4,4'-dicyano-BODIPY identi ed by Vicente and Bobadova-Parvanov as the most stable derivative under acidic conditions. 37,38 The increased stability is believed to be a result of enhanced aromaticity, decreased charge density on the boron, and the formation of a stable 4,4'-dicyano-BODIPY-TFA complex.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous attempts and alternative strategies for completing the synthesis of the platform using the F-BODIPY uorophore, the route was unsuccessful resulting in either BF 2 core removal or complete decomposition (see Supplementary Material), despite there being reports in the literature of similar transformations being successful in the presence of F-BODIPY dyes. [24][25][26][27][28] This documented instability of the BF 2 core [29][30][31][32][33][34][35][36] was overcome by replacing it with the recently reported 4,4'-dicyano-BODIPY identi ed by Vicente and Bobadova-Parvanov as the most stable derivative under acidic conditions. 37,38 The increased stability is believed to be a result of enhanced aromaticity, decreased charge density on the boron, and the formation of a stable 4,4'-dicyano-BODIPY-TFA complex.…”
Section: Discussionmentioning
confidence: 99%
“…Initially our scaffold design comprised of the conventional 4,4′-difluoro-BODIPY fluorophore (Additional file 1 : Scheme S1). Despite numerous attempts and alternative strategies for completing the synthesis of the platform using the F-BODIPY fluorophore, the route was unsuccessful resulting in either BF 2 core removal or complete decomposition (see Additional File), despite there being reports in the literature of similar transformations being successful in the presence of F-BODIPY dyes (Alnajjar et al 2018 ; Tsuji et al 2018 ; Sui et al 2016 ; Compton et al 2019 ; Ieda et al 2014 ). This documented instability of the BF 2 core (Smithen et al 2012 ; Crawford and Thompson 2010 ; Rumyantsev et al 2013 ; Yu et al 2015 ; Urieta et al 2015 ; Liras et al 2016 ; Lundrigan et al 2014 ; Summers et al 2017 ) was overcome by replacing it with the recently reported 4,4′-dicyano-BODIPY identified by Vicente and Bobadova-Parvanov as the most stable derivative under acidic conditions (Nguyen et al 2016 ; Wang et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2) Inspired by the reported adamantly-BODIPY conjugate that functions as a pK a shi indicator dye for CB7, 91 we developed a novel pH-independent push-pull type high-affinity indicator dye (DASAP) for CB7 that functions both in water and in strongly saline buffers. At rst, this design appeared to have overcome both the affinity and the photophysical limits encountered by MDAP, but practice uncovered a fundamental limitation of indicator displacement assay-based sensing for CB7Idye reporter pairs.…”
Section: Discussionmentioning
confidence: 99%